Faktor yang menentukan keputusan konsumen dalam membeli produk di 25:pm coffee kerobokan - Sulistyawan, Ade Kristiyan; Jamin Ariana, I Nyoman; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 1 (2024): Vol.8,No.1,2024, 2024)
The research aims to understand to determine factor product purchase decisions at 25:PM Coffee Kerobokan and to determine the dominant factors in determining product purchase decisions at 25:PM Coffee Kerobokan. This research used 100 respondents, the sample in this study was selected using the accidental sampling method. Data collection techniques in this study were carried out by observation, interviews, questionnaires, documentation, and literature studies. The data analysis technique used is factor analysis using SPSS version 25 for windows. Based on the Likert scale analysis, the results of distributing questionnaires at 25:PM Coffee Kerobokan show that those who have the highest score are the indicators regarding access to 25:PM Coffee Kerobokan which has a score of 4.63 with the Likert scale category strongly agree. This is proven by many consumers who come because of the very strategic location, which is right on the side of the road. The results of factor analysis show that the service quality factor has the largest variance value with other factors of 47.107%, so that the service quality factor is the most dominant contributing factor that determines consumer decisions in purchase products at 25:PM Coffee Kerobokan with seven significant factors, namely : Alertness in serving consumers (X12.2), Reliable service (X11.3), Responsive in dealing with complaints (X12.1), Responsive in handling complaints (X12.3), Trustworthy employees (X11.2), Concerned consumer needs (X14.1), and Skilled in providing information (X13.2).